The Perspective Of The Cordilleran People On The Political, Economic And Socio-Cultural Advantages Of Federalism - Donguiz, Renebeth G. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The government's ideal focus is to prioritize the citizenry's welfare when they intend to implement governance changes. This would include sustainable political, social, and economic development. In terms of political development, the officials must have a robust value system that motivates them to pursue equality, peace, justice, and overall development and implement policies against hostility and abuse. In terms of social development, the country must pursue the advancement of education, health, culture, information, and the environment. In terms of economic, the government must promote trade, employment, investment, infrastructure, technology, and inclusive growth. And Federalism is recently perceived in the Philippines as an ideal form of governance to eliminate dissidence in the country. Federalism is being scrutinized in the Philippines since it has advantages, as observed among first-world countries like the USA, Australia, and Canada and developing countries like Mexico, India, and Brazil. Among these advantages include political advantages in which the regions or states could act independently in constitutionally drawn governance areas. Several social and economic drivers include technology, employment, and efficient use of resources pressing the government to change governance. These would require the regions or states to immediately cope with changes that confront them without relying on the government's bureaucratic system. In this manner, the government becomes closer to the constituents, allowing them to govern themselves, rule based on their own beliefs, culture, and joint problems, and pursue their advancement. For example, the states could issue licenses, provide for public health, conduct elections and form local governments, and look after intra-state trade (Tayeb, 2016). This paper aims to measure the level of agreement of the constituents in the Cordillera Administrative Region (CAR) on the political, social, and economic advantages of Federalism. Moreover, this paper provides theoretical contributions on Federalism since there has been limited literature on Federalism in the Philippines. The study would also provide empirical evidence and findings on Federalism's advantages, particularly in the case of the Cordillera Administrative Region.